The position of Poland in Europe - Kozłowski , Stefan (Problemy Ekorozwoju, 2006)
Strategy of sustainable development of the European Union is largely based on the creation of large-spatial nature structures. In Central-East Europe these are the Carpathian Ecoregion, Green Ring of the Baltic and Green Lungs of Europe initiatives. The Carpathian Convention of 7 countries has been aimed at the development and implementation of the idea of the Green Heart of Europe. It refers mainly to the problems of the natural and cultural environment. The Green Ring of the Baltic includes the areas of the Green Lungs of Poland and Western Pomerania. The structure of the Green Lungs of Poland is functioning very well, as it operates within the frames of the intervoivodship agreement of the GLP, Scientific Council and GLP Foundation. An information bulletin is also issued periodically. The idea of the Green Lungs of Europe was developed in 1992, and now it requires new guidelines. All of these initiatives indicate the very significant role of Poland in the implementation of the strategy of sustainable development in Europe.